(untitled) (Global Journal of Science Frontier Research, 2020)
In this paper, we introduce a different approach to the theory of gravitational field. This method can give the semiclassical graviton directly. We discuss the dynamics and quantization of graviton and obtain the field equation of graviton. Also we give proof to prove that the quantum field theory constructed in this paper is classically equivalent to the general theory of relativity. We obtain the Green’s function of the graviton by the field equation, and the difficulty of Feynman integral divergence can be solved by this method.